Bacillus licheniformis BT5.9 Isolated from Changar Hot Spring, Malang, Indonesia, as a Potential Producer of Thermostable ?-amylase - Darah Ibrahim; Han Li Zhu; Isnaeni; Lim Sheh Hong (Tropical Life Sciences Research, 2013)
A total of 34 bacterial isolates were obtained from soil samples collected from Changar Hot Spring, Malang, Indonesia. Of these, 13 isolates produced a zone of hydrolysis in starch-nutrient agar medium and generated various amylases in liquid medium. One isolate was selected as the best amylase producer and was identified as Bacillus licheniformis BT5.9. The improvement of culture conditions (initial medium pH of 5.0, cultivation temperature of 50°C, agitation speed of 100 rpm and inoculum size of 1.7 × 109 cells/ml) provided the highest amylase production (0.327 U/ml). Sebanyak 34 pencilan bakteria telah diperolehi daripada sampel tanah yang diambil dari Changar Hot Spring, Malang, Indonesia. Daripada jumlah ini, 13 pencilan menghasilkan zon hidrolisis pada medium agar kanji-nutrien dan menghasilkan pelbagai amilase dalam medium cecair. Satu pencilan telah dipilih sebagai pengeluar amilase terbaik dan telah dikenal pasti sebagai Bacillus licheniformis BT5.9. Peningkatan keadaan kultur (pH awal medium 5.0, suhu penanaman 50°C, kelajuan pergolakan 100 rpm dan saiz inokulum sebanyak 1.7 × 109 sel/ml) memberikan penghasilan amilase yang tertinggi (0.327 U/ml).